2005
DOI: 10.1128/aem.71.12.7696-7704.2005
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Fungi Produce Laccases Potentially Involved in Phenol Degradation in Fungus Combs of Fungus-Growing Termites in Thailand

Abstract: Fungus-growing termites efficiently decompose plant litter through their symbiotic relationship with basidiomycete fungi of the genus Termitomyces. Here, we investigated phenol-oxidizing enzymes in symbiotic fungi and fungus combs (a substrate used to cultivate symbiotic fungi) from termites belonging to the genera Macrotermes, Odontotermes, and Microtermes in Thailand, because these enzymes are potentially involved in the degradation of phenolic compounds during fungus comb aging. Laccase activity was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…Phenolic compounds are not only present in live plant tissue, but to a lesser extent also in the shed leaves and leaf litter (24) collected by most other fungus-growing ants, suggesting that polyphenol-oxidase activity was an inherent property of ant fungus farming before active leaf cutting arose. Ant-cultivated leucocoprinaceous fungi are closely related to saprophytic basidiomycetes that mostly decompose leaf litter (25), and laccase enzymes are known from the gardens of leaf-litter collecting fungus-growing termites (26), indicating the inherent need for phenol degradation when using leaf litter as fungal substrate. The genomes of saprophytic fungi normally contain multiple laccase-coding genes (27,28), so that the actual number of laccases that we found in L. gongylophorus may merely represent the enzyme spectrum of the last common ancestor of the gongylidiabearing cultivars (14,29).…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds are not only present in live plant tissue, but to a lesser extent also in the shed leaves and leaf litter (24) collected by most other fungus-growing ants, suggesting that polyphenol-oxidase activity was an inherent property of ant fungus farming before active leaf cutting arose. Ant-cultivated leucocoprinaceous fungi are closely related to saprophytic basidiomycetes that mostly decompose leaf litter (25), and laccase enzymes are known from the gardens of leaf-litter collecting fungus-growing termites (26), indicating the inherent need for phenol degradation when using leaf litter as fungal substrate. The genomes of saprophytic fungi normally contain multiple laccase-coding genes (27,28), so that the actual number of laccases that we found in L. gongylophorus may merely represent the enzyme spectrum of the last common ancestor of the gongylidiabearing cultivars (14,29).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to characteristic ligninolytic peroxidases, laccase is the only enzyme with the potential to act on lignin that has been found in Termitomyces spp. (15,16,21), but its functional role in ligninolysis remains unclear and controversial (22). In addition to genetic and biochemical research approaches, several solid-state NMR studies have shown different peak intensities assigned to lignin structures between spectra of the fresh comb and mature comb (23,24).…”
Section: Significancementioning
confidence: 99%
“…from several Macrotermitinae termite hosts apparently lack typical ligninolytic agents, such as lignin peroxidase (LiP), manganese peroxidase (MnP), and versatile peroxidase (VP), that are found in, for example, white-rot fungi (8,15,16). Research on these enzymes shows that lignin depolymerization may occur via many mechanisms: (i) LiPs and VPs are known to efficiently oxidize nonphenolic β-ether units in lignin within the wood cell wall-beyond where enzymes are permitted to travel-via single electron transfer, creating aryl cation radical intermediates and cleaving the β-ether unit between its Cα and Cβ carbons (17,18); (ii) MnPs preferentially oxidize Mn 2+ to the reactive Mn 3+ which, in its chelated form, can act as a diffusible redox mediator and attack phenolic structures in lignin (19); (iii) unsaturated fatty acids undergo peroxidation by MnP to form organoperoxyl radicals that have also been shown to be potential ligninolytic agents if able to diffuse into the wood cell wall (20).…”
Section: Significancementioning
confidence: 99%
“…Traditional three-domain fungal and bacterial laccases have been widely studied for their importance in various biotechnological applications (13)(14)(15). A novel lineage of relatively small LMCOs-the two-domain LMCOs-has now attracted the attention of researchers (16), and two-domain LMCOs were found to be typically present in Streptomyces spp., such as Streptomyces griseus, Streptomyces ipomoeae, and Streptomyces coelicolor (17)(18)(19)(20).…”
mentioning
confidence: 99%